Tantangan Reformasi Ketatanegaraan di Era Disrupsi Digital: Kajian Literatur Hukum Tata Negara di Indonesia: Penelitian - Kartika, Iis; Haramein, Imam (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Indonesia’s constitutional reform since 1998 has brought fundamental changes to the governance system, constitution, and state administration. However, in the era of digital disruption, new challenges have emerged that demand constitutional law to adapt to the dynamics of information technology. This study aims to analyze the challenges of Indonesia’s constitutional reform amidst digital transformation using a library research approach. Data were obtained from academic literature, constitutional regulations, and public policy documents related to digital governance, e-government, and citizens’ digital rights protection. The findings indicate that the major challenges of constitutional reform in the digital era include: (1) the regulatory gap between conventional law and digital practices, (2) the need to affirm constitutional rights regarding personal data and cybersecurity, (3) weak governmental digital governance, and (4) potential violations of democratic principles through the misuse of information technology. This study emphasizes the urgency of reconstructing a constitutional law paradigm that is adaptive, participatory, and responsive to technological development. Future constitutional reforms should integrate digitalization as an essential component of transparent, accountable, and just state administration.